Thermoregulatory influence of a cooling vest on hyperthermic athletes - Lopez, R. M.; Cleary, M. A.; Jones, L. C.; Zuri, R. E. (Journal of Athletic Training, 2008)
Athletic trainers must have sound evidence for the best practices in treating and preventing heat-related emergencies and potentially catastrophic events.